AN OVERVIEW OF BIOFUELS - Qureshi, I. H.; Ahmad, S. (The Nucleus, 2020)
Biofuels for transport have received considerable attention due to rising oil prices and growing concern about greenhouse gas emissions. Biofuels namely ethanol and esters of fatty acids have the potential to displace a substantial amount of petroleum fuel in the next few decades which will help to conserve fossil fuel resources. Life cycle analyses show that biofuels release lesser amount of greenhouse gases and other air pollutants. Thus biofuels are seen as a pragmatic step towards reducing carbon dioxide emission from transport sector. Biofuels are compatible with petroleum and combustion engines can easily operate with 10% ethanol and 20% biodiesel blended fuel with no modification. However higher concentrations require â€œflex-fuelâ€ engines which automatically adjust fuel injection depending upon fuel mix. Biofuels are derived from renewable biomass and can be produced from a variety of feedstocks. The only limiting factors are the availability of cropland, growth of plants and the climate. Countries with warmer climate can get about five times more biofuel crops from each acre of land than cold climate countries. Genetically modified crops and fast growing trees are being developed to increase the production of energy crops.